Significant Reduction in Thermal Conductivity and Improved Thermopower of Electron‐Doped Ba1–xLaxTiO3 with Nanostructured Rectangular Pores. (15th March 2021) - Ahmed, Al Jumlat; Cortie, David L.; Yun, Frank Fei; Rahman, Yasir; Nazrul Islam, Sheik Md Kazi; Bake, Abdulhakim; Konstantinov, Konstantin; Hossain, Md. Shahriar A.; Alowasheeir, Azhar; Yamauchi, Yusuke; Wang, Xiaolin
Abstract: Electron‐doped BaTiO3 is a less studied n ‐type metal oxide thermoelectric material. In this work, the electrical conductivity of BaTiO3 samples has been improved by introducing La to yield an n ‐type Ba1– x La x TiO3 semiconducting material. Density functional theory calculations show that the optimal electron‐doping occurs at x = 0.2, and this is also confirmed experimentally. To improve the thermoelectric properties further, nanostructured cuboidal pores are introduced into the bulk Ba1– x La x TiO3 using F127 surfactant micelles for a chemical templating process, followed by spark plasma sintering. Interestingly, transmission electron microscopy images and X‐ray powder diffraction analysis confirms that our fabricated samples are cubic BaTiO3 perovskite phase with the nanostructured rectangular‐prism pores of >4 nm. Scanning electron microscopy images show that all the samples have similar grain boundaries and uniform La doping, which suggests that the large reduction in the lattice thermal conductivity in the F127‐treated samples arises primarily from the pore distribution, which introduces anisotropic phonon scattering within the unique nanoarchitecture. The sample with 20 at% La doping and nanopores also shows a thermopower that is doubled compared to the related sample without porosity. Together with the lattice thermal conductivity, enables a significant improvement in figure of merit, zT compared to the other samples. Abstract : Ba1– x La x TiO3 bulk thermoelectric with rectangular nanopores is successfully fabricated by micelle assembly method using surfactant F127, followed by spark plasma sintering process. The nanoscale pores in the bulk sample significantly reduce the phonon thermal conductivity and improve thermopower, which substantially improves the figure of merit.